Michigan Screening and Intervention for Glaucoma and Eye Health Through Telemedicine (MI-SIGHT): Baseline Methodology for Implementing and Assessing a Community-based Program. Issue 5 (15th May 2021) - Newman-Casey, Paula A.; Musch, David C.; Niziol, Leslie M.; Elam, Angela R.; Zhang, Jason; Moroi, Sayoko E.; Johnson, Leroy; Kershaw, Martha; Saadine, Jinan; Winter, Suzanne; Woodward, Maria A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Precis: The Michigan Screening and Intervention for Glaucoma and eye Health through Telemedicine (MI-SIGHT) program leverages community-engaged research, telemedicine, and health coaching to overcome key logistical and psychosocial barriers to improve glaucoma screening in underserved communities. Purpose: To describe the methodology of the implementation and evaluation of the MI-SIGHT Program. Methods: The MI-SIGHT Program uses community engagement, telemedicine, and health coaching to overcome key logistical and psychosocial barriers to glaucoma identification and care among underserved populations. The MI-SIGHT Program will be evaluated in 2 community clinics: Hamilton Community Health Network, a federally qualified health center in Flint, Michigan, and the Hope Clinic, a free clinic in Ypsilanti, Michigan. A Community Advisory Board including the research team and health care providers, administrators, and patients from both clinics will guide program implementation. An ophthalmic technician at the community clinics will conduct screening tests for glaucoma and eye disease. The data will be transmitted through electronic health record to be reviewed by an ophthalmologist who will make recommendations for follow-up care. The ophthalmic technician will conduct a return visit to fit low-or no-cost glasses, help arrange follow-up with an ophthalmologist, and provide education. Those diagnosed with glaucoma or suspected glaucoma will be randomized to standard education or personalized glaucoma education and coaching. Costs will be assessed. Results: The authors hypothesize that the MI-SIGHT Program will detect a higher prevalence rate of glaucoma than that found in the general population, improve upon presenting visual acuity, enhance vision-related quality of life, and demonstrate that personalized glaucoma education and coaching improve adherence to follow-up care. Conclusion: The MI-SIGHT Program may serve as a model for glaucoma screening and care in high-risk communities.